Social choice and legitimacy : the possibilities of impossibility - Patty, John W.; Penn, Elizabeth Maggie, 1977- (Political economy of institutions and decisions., 2014)
Governing requires choices, and hence trade-offs between conflicting goals or criteria. This book asserts that legitimate governance requires explanations for such trade-offs and then demonstrates that such explanations can always be found, though not for every possible choice. In so doing, John W. Patty and Elizabeth Maggie Penn use the tools of social choice theory to provide a new and discriminating theory of legitimacy. In contrast with both earlier critics and defenders of social choice theory, Patty and Penn argue that the classic impossibility theorems of Arrow, Gibbard, and Satterthwaite are inescapably relevant to, and indeed justify, democratic institutions. Specifically, these institutions exist to do more than simply make policy, through their procedures and proceedings, these institutions make sense of the tradeoffs required when controversial policy decisions must be made.